Third-generation rabies viral vectors allow nontoxic retrograde targeting of projection neurons with greatly increased efficiency - Lei Jin; Heather A. Sullivan; Mulangma Zhu; Nicholas E. Lea; Thomas K. Lavin; Xin Fu; Makoto Matsuyama; YuanYuan Hou; Guoping Feng; Ian R. Wickersham (Cell Reports: Methods, 2023)
Summary: Rabies viral vectors have become important components of the systems neuroscience toolkit, allowing both direct retrograde targeting of projection neurons and monosynaptic tracing of inputs to defined postsynaptic populations, but the rapid cytotoxicity of first-generation (ΔG) vectors limits their use to short-term experiments. We recently introduced second-generation, double-deletion-mutant (ΔGL) rabies viral vectors, showing that they efficiently retrogradely infect projection neurons and express recombinases effectively but with little to no detectable toxicity; more recently, we have shown that ΔGL viruses can be used for monosynaptic tracing with far lower cytotoxicity than the first-generation system. Here, we introduce third-generation (ΔL) rabies viral vectors, which appear to be as nontoxic as second-generation ones but have the major advantage of growing to much higher titers, resulting in significantly increased numbers of retrogradely labeled neurons in vivo. Motivation: Rabies viral vectors are useful tools for labeling projection neurons, but first-generation vectors are cytotoxic, and second-generation vectors are difficult to produce at high concentrations, and this limits the numbers of labeled neurons. Here, we introduce third-generation vectors that are both nontoxic and easily grown to high concentrations, allowing labeling of many more neurons in vivo.